Apoptosis-Like Death, an Extreme SOS Response in Escherichia coli - Ariel Erental (American Society for Microbiology, 2014)
ABSTRACT In bacteria, SOS is a global response to DNA damage, mediated by the recA-lexA genes, resulting in cell cycle arrest, DNA repair, and mutagenesis. Previously, we reported that Escherichia coli responds to DNA damage via another recA-lexA-mediated pathway resulting in programmed cell death (PCD). We called it apoptosis-like death (ALD) because it is characterized by membrane depolarization and DNA fragmentation, which are hallmarks of eukaryotic mitochondrial apoptosis. Here, we show that ALD is an extreme SOS response that occurs only under conditions of severe DNA damage. Furthermore, we found that ALD is characterized by additional hallmarks of eukaryotic mitochondrial apoptosis, including (i) rRNA degradation by the endoribonuclease YbeY, (ii) upregulation of a unique set of genes that we called extensive-damage-induced (Edin) genes, (iii) a decrease in the activities of complexes I and II of the electron transport chain, and (iv) the formation of high levels of OH˙ through the Fenton reaction, eventually resulting in cell death. Our genetic and molecular studies on ALD provide additional insight for the evolution of mitochondria and the apoptotic pathway in eukaryotes. IMPORTANCE The SOS response is the first described and the most studied bacterial response to DNA damage. It is mediated by a set of two genes, recA-lexA, and it results in DNA repair and thereby in the survival of the bacterial culture. We have shown that Escherichia coli responds to DNA damage by an additional recA-lexA-mediated pathway resulting in an apoptosis-like death (ALD). Apoptosis is a mode of cell death that has previously been reported only in eukaryotes. We found that E. coli ALD is characterized by several hallmarks of eukaryotic mitochondrial apoptosis. Altogether, our results revealed that recA-lexA is a DNA damage response coordinator that permits two opposite responses: life, mediated by the SOS, and death, mediated by the ALD. The choice seems to be a function of the degree of DNA damage in the cell.